Eighty-eight variants highlight the role of T cell regulation and airway remodeling in asthma pathogenesis - Thorunn A. Olafsdottir (Nature Portfolio, 2020)
Asthma is a common allergic airway disease with significant inter-individual heterogeneity. Here, Olafsdottir et al. report a genome-wide meta-analysis of two large population-based cohorts to identify sequence variants that associate with asthma risk and perform follow-up functional analyses on a protective loss-of-function variant in TNFRSF8.